2022
DOI: 10.3389/fmicb.2022.1009885
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a heat-resistant strain of Lentinus edodes by fungal Hsp20 protein overexpression and genetic transformation

Abstract: The shiitake mushroom (Lentinus edodes) is the second most popular edible mushroom globally due to its rich nutritional value and health benefits associated with consumption. However, the characteristics of growing at low temperatures limit the area and time of its cultivating. We selected a low-temperature cultivar as the original strain. We proposed to construct a heat-shock protein expression vector to achieve genetic transformation in this low-temperature strain to improve the survivability of the strain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…As illustrated in Figure 1 , the close clustering pattern between LY01-LY09 and B. anthracis suggests that LY01-LY09 may be pathogens that are harmful to humans as well. Previous studies have demonstrated that HSP20 exhibits chaperone activity, which can enhance cellular tolerance to damage and maintain normal cellular metabolism under various stresses, thus improving cell survival rates ( Kranzler et al, 2016 ; Ling et al, 2022 ; Niu et al, 2022 ). LY07 and LY09 had more than one Hsp20 genes, some of which undergone point mutations and loss of long amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…As illustrated in Figure 1 , the close clustering pattern between LY01-LY09 and B. anthracis suggests that LY01-LY09 may be pathogens that are harmful to humans as well. Previous studies have demonstrated that HSP20 exhibits chaperone activity, which can enhance cellular tolerance to damage and maintain normal cellular metabolism under various stresses, thus improving cell survival rates ( Kranzler et al, 2016 ; Ling et al, 2022 ; Niu et al, 2022 ). LY07 and LY09 had more than one Hsp20 genes, some of which undergone point mutations and loss of long amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…The optimum growth temperature for L. edodes mycelium ranges from 24 to 27 °C and the lethal temperature could be 38 °C or above, depending on the strain [ 26 ]. Heat stress appears to be the major abiotic constraint inhibiting mycelium growth, disease resistance, and fruiting body development, thereby seriously reducing fruiting body productivity and the quality of L. edodes [ 24 , 53 , 54 , 55 ]. Therefore, it is of great significance to decipher the mechanisms by which L. edodes addresses thermostress.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable number of studies have accumulated over the years addressing the topic of heat resistance in the mycelium of L. edodes [ 15 , 26 , 55 ]. Previous studies have documented that heat shock proteins (HSPs), indoleacetic acid (IAA), catalase, and trehalose play crucial roles in the thermotolerance of L. edodes [ 15 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the search for BlastP hits of this protein reveals its presence in T. brumale, T. aestivum, T. indicum, T. magnatum, and many other ascomycetes. This protein has been used to construct a temperature-tolerant strain of Lentinula edodes [38] and found in tandem repeats in a temperature-adapted Coriolopsis trogii. The model identified in T. borchii corresponds to a secreted protein.…”
Section: Rna-seq and Transcriptome Analysismentioning
confidence: 99%